Antimicrobial resistance in odontogenic infections A protocol for systematic review - CUEVAS-GONZALEZ, MARIA VERONICA (2022)
It is estimated that up to 90% of head and neck infections have an odontogenic origin, which are considered among the most common in the oral cavity and maxillofacial region. Bacterial resistance has been 1 of the main problems related to the treatment of this type of infection in recent years. The frequency of this resistance is increasing, which is mainly due to patient self-medication and the mutations that bacteria present. Therefore, the objective of this study is to analyze the antimicrobial resistance of antibiotics commonly administered for the treatment of odontogenic infections.